33 ARE CLINICAL TRIALS RANDOMISING HOUSEHOLDS TO LIFESTYLE INTERVENTIONS FOR THE PREVENTION OF COGNITIVE DECLINE FEASIBLE?. (18th November 2021) - Costello, M; McCarthy, C; Bosch, J; Robinson, S; Canavan, M; O'Donnell, M
Abstract: Background: Dementia is increasing in prevalence worldwide. Several lifestyle factors have been identified as targets for dementia prevention, which may be more effective if targeted at households instead of an individual. To date there have been no clinical trials randomising households to lifestyle interventions of sleep, diet and/or physical activity to prevent cognitive decline. To inform future studies, qualitative approaches can give valuable in-depth insights into the values and beliefs of all household members towards behavioural change. Methods: Semi structured interviews were carried out among eight households affected by cognitive impairment. Interview content was analysed, and important themes identified. Results: Eighteen participants were interviewed within household pods. Among those, eight had cognitive impairment and the remainder were spouses or first-degree relatives living in the same home. Several themes of interest emerged including household members without dementia were more likely to report poor sleep habits; sleep was perceived the hardest behaviour to change; although most participants had healthy diets, most were interested in making a change and felt there was a strong link with nutrition and cognition; physical activity is challenging to adapt due to lack of motivation and focus when individuals are cognitively impaired and motivation to pursue physical activity in households centred on relaxation and social interaction. Conclusion: This study identified beliefs and preferences of households towards lifestyle intervention trials. Barriers to study participation including risk of harm, complexity of intervention and deviation from routine emerged during discussions. Findings from this study should be used to inform future clinical trial protocols and future qualitative studies should explore acceptability and feasibility of digital intervention applications.